2015
DOI: 10.12816/0031232
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracoscopic Surgery for the Treatment of First-Time Spontaneous Pneumothorax versus Conservative Treatment

Abstract: Background and aim of the work: Recent studies have shown that video-assisted thoracoscopy (VATS) is safe and beneficial as first time treatment for patients presenting with primary spontaneous pneumothorax (PSP). In this study we will compare the outcome of patients presenting with first time PSP treated by VATS with those treated conservatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…This coincides with the classical rate of recurrence of 20-60% (13). Several studies (14,15) have chosen to treat patients with spontaneous pneumothorax with upfront thoracoscopic blebectomy/ bullectomy and/or pleural abrasion/pleurectomy without inserting a chest drain. This practice is well established in patients with recurrent spontaneous pneumothorax or patients at considerable risk like patients with occupational hazards (divers, pilots etc.).…”
Section: Editorialsupporting
confidence: 58%
“…This coincides with the classical rate of recurrence of 20-60% (13). Several studies (14,15) have chosen to treat patients with spontaneous pneumothorax with upfront thoracoscopic blebectomy/ bullectomy and/or pleural abrasion/pleurectomy without inserting a chest drain. This practice is well established in patients with recurrent spontaneous pneumothorax or patients at considerable risk like patients with occupational hazards (divers, pilots etc.).…”
Section: Editorialsupporting
confidence: 58%
“…Clinical study AL-ALAWI [17] AL-MOURGI [18] ANDERSEN [19] CASALI [10] CHAN [12] CHEN [20] CHEN [21] CHEN [22] GANESALINGAM [9] HARVEY [23] KARASAKI [25] KIM [26] KUAN [27] LICHTER [28] LIGHT [29] MARTÍNEZ-RAMOS [30] MEHTA [31] NISHIUMA [32] NOH [33] NOH [34] OLESEN [6] OUANES-BESBES [13] PRIMAVESI [8] SADIKOT [ due to nutritional deficiencies affecting α 1 -antitrypsin levels or due to unbalanced physical development, was supported by two papers [5,6,[44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…68 There have now been two RCTs of early VATS compared to conservative management after first PSP: the first by Al-Mourgi and Alshehri 69 was a small trial of 41 patients, in which the VATS group underwent surgery within 24 hours of admission to hospital compared to "conservative" treatment with chest tube drainage. 69 They found no recurrence (0%) in the VATS group, compared to 40.9% in the conservative group, which is higher than previously reported. 29,30 The second larger RCT by Olesen et al 70 enrolled 373 PSP patients again showed a significant lower recurrence rate in those treated with VATS (13%) compared to conservative treatment (34%).…”
Section: Recurrence Prevention After First Occurrence?mentioning
confidence: 63%